An investigation of non-prescription medicine supply in community pharmacies in Hanoi, Vietnam - Do, Xuan Thang (2013)
Supplying safe, appropriate and effective non-prescription medicines for customers in community pharmacies is a key role of pharmacists and pharmacy assistants in every country. However, in low and middle-income countries, including Vietnam, the quality of professional services from pharmacies is limited, unclear and has often been questioned. There is limited research about the real situation surrounding non-prescription medicine supply in community pharmacies in Vietnam. The factors that influence the supply of non-prescription medicines to customers and to what extent the service provision could be improved for the benefit of pharmacy customers needs to be explored. This study aimed to investigate non-prescription medicines supply in community pharmacies in Hanoi, Vietnam in order to provide scientific evidence about the situation.